(untitled) (Research, Society and Development, 2020)
This article began with an interest in finding out about the knowledge of nursing professionals regarding the prescription of medicines within Primary Health Care, emphasizing the variety of medicines that the professional nurse can prescribe, respecting the protocols established by the Ministry of Health. It is a systematic review study with a qualitative approach, which had the objectives of identifying the autonomy and difficulties that nurses in the Family Health Strategy face in the prescriptive act. As a result, it was noted that there are few published articles on this topic, in addition to emphasizing the importance of deepening the subjects focused on pharmacology and prescription within the undergraduate program, in order to reduce the insecurity existing in the prescriptive act and decrease the feeling of occupational invasion that some professionals feel when prescribing. We conclude that even though nurses are aware of their prescriptive rights within the FHS, it is necessary to discuss more about nursing performance in relation to drug prescription.